Life in the Goldilocks Zone: Perceptions of Place Disruption on the Periphery of the Bakken Shale. Issue 2 (1st February 2018) - Junod, Anne N.; Jacquet, Jeffrey B.; Fernando, Felix; Flage, Lynette
ABSTRACT: Community impacts from oil development in the Bakken Shale, located in the north central region of the United States, have been well reported in the press, including highly publicized accounts of social disruption. Less examined are communities on the periphery of such development, which experience related impacts unique to their location. Twenty-eight long-time residents from three Bakken periphery communities were interviewed to evaluate social and environmental impact perceptions, including perceived risks of place disruption. Findings suggest that whereas place meanings and identities were disrupted by the oil boom in Bakken core communities, they remain intact in these periphery communities. Findings further suggest periphery residents view their proximal location to the Bakken region as a social and economic "Goldilocks Zone:" close enough to benefit from spillover economic impacts, yet far enough away to avoid serious negative social impacts. This research extends understanding of place disruption and development impacts in energy periphery communities.